HIF-1α signaling activation by post-ischemia treatment with astragaloside IV attenuates myocardial ischemia-reperfusion injury. - Jingwen Si; Ning Wang; Huan Wang; Juan Xie; Jian Yang; Hui Yi; Zixuan Shi; Jing Ma; Wen Wang; Lifang Yang; Shiqiang Yu; Junchang Li (PLoS ONE)
In this study, we evaluated the effect of astragaloside IV (Ast IV) post-ischemia treatment on myocardial ischemia-reperfusion (IR) injury (IRI). We also examined whether hypoxia inducible factor-1α (HIF-1α) and its downstream gene-inducible nitric oxide (NO) synthase (iNOS) play roles in the cardioprotective effect of Ast IV. Cultured cardiomyocytes and perfused isolated rat hearts were exposed to Ast IV during reperfusion in the presence or absence of the HIF-1α inhibitor 2-methoxyestradiol (2-MeOE2). The post-ischemia treatment with Ast IV protected cardiomyocytes from the apoptosis and death induced by simulated IRI (SIRI). Additionally, in cardiomyocytes, 2-MeOE2 and HIF-1α siRNA treatment each not only abolished the anti-apoptotic effect of post-ischemia treatment with Ast IV but also reversed the upregulation of HIF-1α and iNOS expression. Furthermore, after treatment with Ast IV, post-ischemic cardiac functional recovery and lactate dehydrogenase (LDH) release in the coronary flow (CF) were improved, and the myocardial infarct size was decreased. Moreover, the number of apoptotic cells was reduced, and the upregulation of the anti-apoptotic protein Bcl2 and downregulation of the pro-apoptotic protein Caspase3 were reversed. 2-MeOE2 reversed these effects of Ast IV on IR-injured hearts. These results suggest that post-ischemia treatment with Ast IV can attenuate IRI by upregulating HIF-1α expression, which transmits a survival signal to the myocardium.